STRATEGI PENINGKATAN NASABAH BANK SYARIAH DENGAN PENDEKATAN EXPERIENTAL MARKETING (STUDI PADA BANK MUAMALAT KCP BONE) - Julianti Putri, Helma; Munawarah, Munawarah (Faculty of Islamic Economics and Business, 2022)
The objectives of this study are: (1) to find out how the form of the Experiental Marketing implementation strategy carried out by Bank Muamalat KCP Bone in increasing the number of customers (2) to find out and analyze the constraints of Bank Muamalat KCP Bone in increasing the number of customers through an Experiental Marketing approach and solutions to overcome these obstacles. This type of research is field research with qualitative research methods and descriptive approaches. Data were collected through observation, interviews, and documentation. The data obtained are analyzed using data reduction methods, data presentation and inference. At Bank Muamalat KCP Bone, the form of strategy for implementing Experiental Marketing carried out in increasing prospective customers is by approaching emotionally to prospective customers/ customers, conducting ball pick-up services to prospective customers through the